The impact of the multiplicity of syntactic aspects in the poetic evidences, fixing the imbalance of Ibn al-Sayyid al-Andalusi (522 AH) - zehar, Mohammed (The Notebooks of the Algerian Poetics Laboratory Journal, 2025)
The relationship between syntaxe and meaning is a close relationship asthe validity of one is based on the integrity of the other, and th e multiplicity of the expression leads to a multiplicity of meaning and vice versa, as the meaning in many places leads to directing the expression to a face with which the meaning is correct or elevated. Due to the importance of this relationship, many scholars, in the past and present have been studying it and Demonstrating its importance in guiding texts, especially the texts and readings of expression and Poetry had a share of these studies, and it appeared in the past in several books, including books of grammar when they dealt with poetic evidence, including books dealing with this topic especially what he called the verses of meanings and the books by ibnesseyed-el andalloussi( 522H) and it was followed in many positions of the direction of meaning. And study it. . The conclusion included the research fndings and recommendations